Evaluation of the French medical practices in endometrial cancer management by using quality indicators. (May 2019) - Larouzée, E.; Phelippeau, J.; Roberti, E.; Koskas, M.
Abstract: Study objective: To evaluate the French quality of care of endometrial cancer using published relevant quality indicators and researche explanatory factors influencing its management. Study design: We used databases from the "Echantillon Généraliste de Bénéficiaires", sample of the French population, to identify cases operated on between 2005–2014. Quality indicators evaluated were: three years survival rate, time between surgery and adjuvant treatment, use of IRMT and 3DCRT for radiotherapy, rate of minimally invasive surgery. Multilevel analysis was performed to identify explanatory factors. Results: 405 women were included. 323 had a follow-up of more three years, and 250 were alive at three years (77.0%). 70 (17.3%) underwent minimally invasive surgery. 73 women of the 153 who received adjuvant treatment (47.8%) started it within 60 days after surgery. Among the 60 patients who received adjuvant radiotherapy, 50 (83.3%) underwent the IRMT or 3DCRT technique. In multilevel analysis, diabetes (OR = 1.24: 95% CI [1.08; 1.41]), and age under 65 (OR = 1.15: 95% CI [1.01; 1.35]) were associated with an increase of the three years survival rate. Lymphadenectomy (OR = 1.12: 95% CI [1.03; 1.22]), and management in an university institution (OR = 1.13: 95% CI [1.01; 1.25]) were associated with adequate technique for the adjuvant radiotherapy. Laparoscopic surgery increased after 2010 (OR = 1.18: 95% CI [1, 10; 1, 25]). Conclusion: Improvements should be made to increase the rate of laparoscopy and reduce the delay before adjuvant treatment for the management of endometrial cancer in France, specifically in non-university centers.